2014
DOI: 10.1016/j.jamda.2013.12.084
|View full text |Cite|
|
Sign up to set email alerts
|

Delirium Superimposed on Dementia Strongly Predicts Worse Outcomes in Older Rehabilitation Inpatients

Abstract: ObjectiveDelirium superimposed on dementia (DSD) is common in many settings. Nonetheless, little is known about the association between DSD and clinical outcomes. The study aim was to evaluate the association between DSD and related adverse outcomes at discharge from rehabilitation and at 1-year follow-up in older inpatients undergoing rehabilitation.DesignProspective cohort study.SettingHospital rehabilitation unit.ParticipantsA total of 2642 patients aged 65 years or older admitted between January 2002 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 42 publications
4
107
1
5
Order By: Relevance
“…In fact, compared to these 3 studies, the mean age of patients with dementia in our study was much higher, probably raising the mortality rate of those with dementia without delirium and attenuating differences compared to DSD. Regarding functional evolution, our results are consistent with those of previous studies [31, 35, 36], showing a greater functional decline among patients with delirium, and also with Morandi et al [20], who observed a greater disability in patients that developed DSD than in those with only dementia or only delirium in a hospital rehabilitation setting.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, compared to these 3 studies, the mean age of patients with dementia in our study was much higher, probably raising the mortality rate of those with dementia without delirium and attenuating differences compared to DSD. Regarding functional evolution, our results are consistent with those of previous studies [31, 35, 36], showing a greater functional decline among patients with delirium, and also with Morandi et al [20], who observed a greater disability in patients that developed DSD than in those with only dementia or only delirium in a hospital rehabilitation setting.…”
Section: Discussionsupporting
confidence: 93%
“…Among factors predisposing to delirium, dementia appears to be the most consistent in hospitalized patients [13, 14], and the prevalence of delirium superimposed on dementia (DSD) is almost 90% in some hospital-based studies [15-17]. Patients who develop DSD have an increased risk of longer hospital stay, morbidity, acceleration of cognitive and functional decline, institutionalization, and mortality [18-20]. …”
Section: Introductionmentioning
confidence: 99%
“…This in-hospital rehabilitation setting has been fully described elsewhere. 17,18 Briefly, the rehabilitation ward is staffed by full-time geriatricians, psychiatrists, nurses, nurse aides, and physical, speech, and occupational therapists. Patients were excluded if they were unable to complete study assessments because of delirium, comatose state, or aphasia, based on medical record documentation.…”
Section: Methodsmentioning
confidence: 99%
“…Delirium has been previously described to be negatively associated with functional status in older patients admitted to rehabilitation settings and, in particular, when delirium occurs in the context of dementia. [27][28][29] Conversely, the literature on the association between ACE inhibitors and functional status is controversial. Observational studies have shown that the use of ACE inhibitors is associated with a slower decline in muscle mass, muscle strength, and walking speed in older communitydwelling subjects, suggesting a direct role of these medications on skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%